Exploration of global brand value announcements and market reaction - Khuram Shafi; Zartashia Hameed; Usama Qadri; Samina Nawab (Administrative Sciences, 2018)
Brand value is an intangible asset of all firms and plays an important role in a firm's performance. Many independent firms publish the brand values of the different leading firms worldwide. Here a very simple and basic question is raised; should stockholders and investors consider and analyze brand value when they invest or not. The main objective of this study is to consider this basic question. To answer this question we considered the Global top firms in the period from September 2009 to October 2014. Results are positively significant concerning signaling theory and, it is concluded, in the context of signaling theory, that famous value brands have very important marketplace signals that can help to improve information asymmetry. Investors and stockholders can use this information regarding their investment.
Keywords: 350; Interbrand; stock market reactions; event study; brand value; signaling theory